2017
DOI: 10.1186/s40562-017-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of the earthquake hazard along the Himalaya: constraints in bracketing of medieval earthquakes from paleoseismic studies

Abstract: The Himalaya is one of the most seismically active regions of the world. (Mw 7.8) are the testimony to ongoing tectonic activity. In the last few decades, tremendous efforts have been made along the Himalayan arc to understand the patterns of earthquake occurrences, size, extent, and return periods. Some of the large magnitude earthquakes produced surface rupture, while some remained blind. Furthermore, due to the incompleteness of the earthquake catalogue, a very few events can be correlated with medieval e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Grey dashed bars indicate synchronous slip in single earthquakes with surface ruptures exceeding 200 km proposed variously by Mugnier et al (2013), Rajendran et al (2018b) and Wesnousky et al (2019). A, Arora & Malik (2017), ; Malik et al ( , 2008Malik et al ( , 2010a; B, Kumahara & Jayangondaperumal (2013); C, Kumar et al (2006) strain. For example, if the region of preseismic strain accumulation is only 20 km wide, the maximum slip that can be stored and released, no matter how long the interval since the previous earthquake, is only 2 m (20 km × 10 −4 strain).…”
Section: Palaeoseismic Studies Of Great Earthquakesmentioning
confidence: 96%
See 1 more Smart Citation
“…Grey dashed bars indicate synchronous slip in single earthquakes with surface ruptures exceeding 200 km proposed variously by Mugnier et al (2013), Rajendran et al (2018b) and Wesnousky et al (2019). A, Arora & Malik (2017), ; Malik et al ( , 2008Malik et al ( , 2010a; B, Kumahara & Jayangondaperumal (2013); C, Kumar et al (2006) strain. For example, if the region of preseismic strain accumulation is only 20 km wide, the maximum slip that can be stored and released, no matter how long the interval since the previous earthquake, is only 2 m (20 km × 10 −4 strain).…”
Section: Palaeoseismic Studies Of Great Earthquakesmentioning
confidence: 96%
“…They invoke arguments ranging from the observation that such a large earthquake is unknown in India's history, that creep processes absorb India's convergence, or that physical segmentation of the Himalaya prevents through-going propagation of ruptures longer than a few hundred kilometres (e.g. Srivastava et al 2013;Gupta & Gahalaut 2015;Arora & Malik 2017). However, support for each of the above constraints is subjective or weak, and in some cases, demonstrably wrong.…”
Section: Limits To Himalayan Earthquake Magnitudes?mentioning
confidence: 99%
“…Earth hazard geosciences span the interface of the earth and human and social sciences. The former is generally concerned with an analysis of potentially hazardous events and processes such as earthquakes, tsunamis, droughts, bushfires, and so on, seeking to understand their causes, processes, distributions, frequencies, magnitudes, intensities, past histories, likely future occurrence, impacts, and effects (Arora and Malik 2017;Hyndman and Hyndman 2014;Nott 2016;Somerville 2014). Experts are interested in observing, measuring, monitoring, modelling, and forecasting these potentially hazardous events.…”
Section: Fig 1 Critical Debates About the Anthropocene And Reflectivmentioning
confidence: 99%
“…By conducting trenching surveys across active faults, occurrence of past surface ruptures or earthquakes can be examined. Arora and Malik (2017) compiled the paleoseismological data from numerous trenches excavated by previous workers along the entire Himalaya arc and recalibrated the radiocarbon ages. They showed that the pattern of past earthquake scenarios consists of overlapping multiple earthquakes with an average rupture length of ~ 300 km (Mw 7.8-8.0), rather than two or three giant earthquakes rupturing the entire Himalayan arc.…”
Section: Paleoseismologymentioning
confidence: 99%